Demolding film with antistatic layer
By providing an antistatic layer on the substrate of the release film with a slip-free coating layer, the problem of deterioration of smoothness and easy shedding caused by the antistatic layer in the prior art is solved, and efficient demolding performance and antistatic properties are achieved.
Patent Information
- Application Number
- CN202380053951.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-19
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-04
AI Technical Summary
The antistatic release film in the prior art can easily lead to deterioration of the smoothness of the surface of the release layer during use, curing obstacles and deterioration of the release performance, and the antistatic layer can easily fall off, resulting in the generation of foreign matter.
An antistatic layer consisting of an antistatic agent and a heat-curing binder resin is used. By setting an antistatic layer on the substrate between the easy-slip coating layer, the adhesion and slipibility of the antistatic layer and the substrate are improved, ensuring that the antistatic layer is not easily shedded during long-term storage and transportation.
It realizes the generation of pinholes, prevents local thickness deviations, reduces uncoiled charge, ensures excellent mold release performance, and prevents the antistatic layer from falling off during friction.
Smart Images

Figure BDA0005242955880000141 
Figure BDA0005242955880000421 
Figure BDA0005242955880000431
Abstract
Description
Technical Field
[0001] The present invention relates to a release film for producing ceramic green sheets. More specifically, it relates to a release film with an antistatic layer that can suppress the generation of pinholes, prevent local thickness deviation, and reduce unwinding static electricity even when a resin sheet such as a ceramic green sheet is thinned. In particular, it relates to a release film for producing ceramic green sheets. Background Art
[0002] Generally, in the manufacturing process of laminated ceramic capacitors, ceramic slurry is formed on a release film and temporarily rolled up before proceeding to the next process. In recent years, with the development of thin-film ceramic green sheets, not only the smoothness of the release layer surface has attracted attention, but also the smoothness of the back side of the release film (the side opposite to the release layer is referred to as the back side of the release film) has attracted attention because the release film is in contact with the ceramic green sheet in a rolled state.
[0003] On the other hand, a release film with a high surface smoothness may cause blocking when wound into a roll, and may easily cause problems such as static electricity when unwinding the roll. In order to prevent such problems, it is known to impart an antistatic function to a release film by including an antistatic agent or the like.
[0004] For example, Patent Documents 1 and 2 disclose a technique of providing an antistatic layer on the release layer side to impart an antistatic function.
[0005] Furthermore, Patent Document 3 discloses a technique for imparting an antistatic function to the back surface of a film.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-224011
[0009] Patent Document 2: Japanese Patent Application Publication No. 2003-251756
[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 02-073833 (Japanese Patent Application No. 7-68388) Summary of the invention
[0011] Problem that the invention aims to solve
[0012] In the antistatic release film disclosed in Patent Document 1, components contained in the antistatic layer may aggregate, and the surface smoothness of the release layer may be deteriorated. Curing inhibition due to the influence of the antistatic layer may lead to deterioration of release performance.
[0013] Similarly, in the antistatic film disclosed in Patent Document 2, since an antistatic agent is added to the release layer, there is a possibility that the release performance may be deteriorated.
[0014] In the antistatic release film disclosed in Patent Document 3, an antistatic layer is formed by coating an alkyl ammonium salt or the like on the substrate of the release film by in-line coating during film formation of the substrate in order to impart antistatic properties to the release film. By providing the antistatic layer on the back side, the adverse effect on the surface of the release layer disappears, but the surface of the antistatic layer is difficult to slide, so the antistatic layer is easily detached due to contact with a guide roller or the like during molding of the ceramic green sheet, and this may also cause the generation of foreign matter.
[0015] Furthermore, in recent years, it is believed that the demand for release films for manufacturing laminated ceramic capacitors has increased in various countries around the world, and the product delivery time has become longer. During long-term storage in a rolled state, stress is applied to the film, which may cause the antistatic layer to fall off, thereby deteriorating the antistatic property and lubricity.
[0016] The present invention is accomplished against the background of the above-mentioned problems in the prior art. That is, the object of the present invention is to provide a release film having an antistatic layer, wherein the antistatic layer has a highly smooth release surface and a back surface, has good peelability, antistatic properties, slipperiness, and adhesion, has excellent antistatic properties and slipperiness after long-term storage, and is difficult to fall off even when rubbed.
[0017] Solutions for solving problems
[0018] The present invention can be shown in the following aspects.
[0019] [1] A release film with an antistatic layer, comprising: a substrate, an antistatic layer provided on one surface of the substrate via a first functional layer, and a release layer provided on the other surface of the substrate.
[0020] The antistatic layer is a layer formed of an antistatic layer-forming composition containing an antistatic agent and a thermosetting binder resin, wherein the antistatic agent contains a conductive polymer.
[0021] The surface resistivity (logΩ / □) of the side provided with the antistatic layer is 3 or more and 10 or less.
[0022] [2] The release film with an antistatic layer according to [1], wherein the substrate does not substantially contain inorganic particles.
[0023] The first functional layer is a slippery coating layer.
[0024] The aforementioned easy-slip coating layer comprises particles,
[0025] The antistatic layer is disposed on one surface of the substrate via the easy-slip coating layer.
[0026] [3] The release film with an antistatic layer according to [1] or [2], wherein the conductive polymer is a polythiophene-based conductive polymer.
[0027] [4] The release film with an antistatic layer according to any one of [1] to [3], wherein the thermosetting binder resin comprises at least one selected from acrylamide resin, melamine resin, polycarbodiimide resin and oxazoline resin.
[0028] [5] A release film with an antistatic layer according to any one of [1] to [4], wherein in the antistatic layer, when the total solid content of the conductive polymer and the thermosetting binder resin is set to 100 mass%, the content of the thermosetting binder resin is greater than 40 mass% and less than 95 mass%.
[0029] [6] A release film with an antistatic layer according to any one of [1] to [5], wherein the surface roughness Sa of the surface of the antistatic layer opposite to the substrate is greater than 1 nm and less than 25 nm, and the maximum protrusion height P is greater than 60 nm and less than 500 nm.
[0030] [7] A release film with an antistatic layer according to any one of [1] to [6], wherein the surface roughness Sa of the surface of the release layer opposite to the substrate is greater than 0.1 nm and less than 5 nm, and the maximum protrusion height P is greater than 1 nm and less than 50 nm.
[0031] [8] A release film with an antistatic layer according to any one of [1] to [7], wherein the charge on the release film when it is unwound at a speed of 100 m / min after being stored at 40°C and a humidity of 50% or less for 30 days is greater than -2 kV and less than +2 kV.
[0032] Effects of the Invention
[0033] According to the present invention, a release film with an antistatic layer is provided, which has all the characteristics of suppressing pinhole generation, preventing local thickness deviation, and reducing unwinding charge even when the ceramic green sheet is thinned, and is suitable for manufacturing resin sheets, such as ceramic green sheets. DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described in detail.
[0035] The release film with an antistatic layer of the present invention comprises a substrate, an antistatic layer provided on one surface of the substrate via a first functional layer, and a release layer provided on the other surface of the substrate.
[0036] The antistatic layer is a layer formed of an antistatic layer-forming composition containing an antistatic agent and a thermosetting binder resin.
[0037] Antistatic agents include conductive polymers.
[0038] The surface resistivity (logΩ / □) of the side provided with the antistatic layer is 3 or more and 10 or less.
[0039] In one embodiment, the release film with an antistatic layer of the present invention is a release film with an antistatic layer for producing a ceramic green sheet. (Hereinafter, it may be referred to as a release film with an antistatic layer.)
[0040] The release film with an antistatic layer of the present invention can suppress the deterioration of the smoothness of the release layer surface and suppress the curing hindrance of the release layer caused by the influence of the antistatic layer. Therefore, the present invention can exhibit excellent release performance while having antistatic properties.
[0041] In addition, the present invention does not contain an antistatic agent in the release layer, so the release layer can exhibit high smoothness, hardness, and release properties without reducing the release performance.
[0042] Furthermore, the surface of the antistatic layer of the present invention can show easy slip. Moreover, the present invention can also suppress the detachment of the antistatic layer that may be generated due to contact with guide rollers during the molding of the ceramic green sheet. Therefore, the generation of foreign matter during the molding of the ceramic green sheet can also be suppressed.
[0043] Furthermore, the present invention is suitable for long-term storage and transportation in a roll state, for example, when a release film is transported from Japan to overseas, and can suppress, for example, the antistatic layer from falling off the film during transportation.
[0044] (Base material)
[0045] The film preferably used as the substrate in the present invention is a film made of a polyester resin, preferably a polyester film mainly containing at least one selected from polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. In addition, it may be a film formed of a polyester copolymerized with a third component monomer as a part of the dicarboxylic acid component or diol component of the above-mentioned polyester. Among these polyester films, polyethylene terephthalate film is most preferred from the perspective of the balance between physical properties and cost.
[0046] In addition, the polyester film may be a single layer or a multilayer. In addition, various additives may be contained in the polyester resin in each layer as required as long as the desired effect of the present invention is exerted. Examples of additives include antioxidants, light stabilizers, anti-gelling agents, organic wetting agents, antistatic agents, ultraviolet absorbers, and the like.
[0047] The polyethylene terephthalate film as the substrate in the present invention does not substantially contain particles with a particle size of 1.0 μm or more. When the substrate has a multilayer structure, the layer forming the surface in contact with the release layer does not substantially contain particles with a particle size of 1.0 μm or more. Hereinafter, in any case where the substrate has a single-layer or multilayer structure, the layer forming the surface in contact with the release layer is expected to show the following manner.
[0048] In addition, particles having a particle size of less than 1.0 μm and greater than 1 nm may be present in the substrate. By making the substrate substantially free of particles having a particle size of greater than 1.0 μm, such as inorganic particles, the release layer can exhibit high smoothness and release properties, and can reduce the transfer of particle shapes in the substrate to resin sheets such as green sheets and the generation of defects.
[0049] In one embodiment, the substrate also does not contain particles having a particle size of less than 1.0 μm, thereby more effectively preventing the particle shape in the substrate from being transferred to the resin sheet and causing a problem.
[0050] In one embodiment, the substrate of the present invention, for example, the polyethylene terephthalate film, is preferably a film that does not substantially contain inorganic particles. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet and causing problems.
[0051] For example, it is preferable that the substrate substantially does not contain particles having a particle size of less than 1.0 μm also substantially does not contain particles having a particle size of 1.0 μm or more.
[0052] Here, in the present invention, "substantially free of particles" means: for example, in the case of inorganic particles smaller than 1.0 μm, when the inorganic elements are quantified by fluorescent X-ray analysis, the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit. This is because even if particles are not actively added to the film, sometimes contaminant components from foreign matter, dirt attached to the production line and equipment in the manufacturing process of the raw resin or film will be peeled off and mixed into the film. In addition, "substantially free of particles with a particle size of 1.0 μm or more" means that particles with a particle size of 1.0 μm or more are not actively contained.
[0053] (Antistatic layer)
[0054] The release film with antistatic layer of the present invention has an antistatic layer arranged on one surface of a substrate across the first functional layer. By stacking the antistatic layer, the attachment of foreign matter can be suppressed, and then the poor peeling caused by electrostatic force can be suppressed. As described later, by arranging the antistatic layer across the first functional layer, the adhesion of the antistatic layer and the substrate can be improved, and then the effect of suppressing the falling off of the antistatic layer is also improved.
[0055] Furthermore, the antistatic layer of the present invention also has slip properties.
[0056] The antistatic layer is a layer formed by an antistatic layer-forming composition comprising an antistatic agent and a thermosetting binder resin. In one embodiment, the antistatic layer-forming composition is a layer formed by curing a composition comprising a conductive polymer and a thermosetting binder resin. Such a composition is sometimes referred to as an antistatic layer-forming composition.
[0057] There is no particular limitation on the method for laminating the antistatic layer, and known methods such as coating, vacuum deposition, lamination, etc. can be used. For example, from the perspective of shortening the production process and stably forming a film, it is preferably provided by coating a coating solution containing an antistatic agent.
[0058] The antistatic layer of the present invention is a layer formed of an antistatic layer-forming composition containing an antistatic agent and a thermosetting binder resin, and the antistatic agent contains a conductive polymer.
[0059] (Conductive polymer)
[0060] The conductive polymer in the present invention is a polymer that can impart antistatic properties, and can use polymers that utilize ion conduction such as cationic compounds, π-electron conjugated conductive polymers, etc. From the viewpoint of antistatic properties under low humidity, it is preferred to use π-electron conjugated conductive polymers. In addition, π-electron conjugated conductive polymers can maintain antistatic properties at a high level without relying on moisture in the air, and therefore have good antistatic properties under various use environments of the film, so they are preferred.
[0061] In addition, an antistatic agent may be used in combination within the range that the effect exerted by the conductive polymer of the present invention is not impaired. As the antistatic agent, polymers utilizing ion conduction such as cationic compounds other than the conductive polymer of the present invention, π-electron conjugated conductive polymers, surfactants, silicon oxide compounds, conductive metal compounds, etc. may also be used.
[0062] As the π-electron conjugated conductive polymer, there can be listed aniline-based polymers containing aniline or its derivatives as structural units, pyrrole-based polymers containing pyrrole or its derivatives as structural units, acetylene-based polymers containing acetylene or its derivatives as structural units, thiophene-based polymers containing thiophene or its derivatives as structural units, etc. If high transparency is desired, as the π-electron conjugated conductive polymer, it is preferred that the polymer does not have nitrogen atoms, wherein, from the viewpoint of transparency, the thiophene-based polymer containing thiophene or its derivatives as structural units is suitable. Preferably, the conductive polymer is a polythiophene-based conductive polymer, and polyalkylene dioxythiophene is particularly suitable. As polyalkylene dioxythiophene, polyethylene dioxythiophene, polypropylene dioxythiophene, poly (ethylene / propylene) dioxythiophene, etc. can be listed.
[0063] It should be noted that, in order to improve the antistatic property of a thiophene-based polymer containing thiophene or its derivatives as a structural unit, for example, 0.1 to 500 parts by mass of a dopant may be added to 100 parts by mass of the polymer containing thiophene or its derivatives as a structural unit. In most cases, there is a problem that the antistatic property is reduced because electron movement becomes difficult. On the contrary, in a few cases, there is a problem that the dispersibility in the solvent is reduced. Examples of the dopant include LiCl, R 1-30 COOLi(R 1-30 : a saturated hydrocarbon group having 1 to 30 carbon atoms), R 1-30 SO3Li、R 1- 30 COONa, R 1-30 SO3Na、R 1-30 COOK, R 1-30 SO3K, tetraethylammonium, I2, BF3Na, BF4Na, HClO4, CF3SO3H, FeCl3, tetracyanoquinoline (TCNQ), Na2B 10 Cl 10 , phthalocyanine, porphyrin, glutamic acid, alkyl sulfonate, polystyrene sulfonate Na (K, Li) salt, styrene / styrene sulfonate Na (K, Li) salt copolymer, polystyrene sulfonate anion, styrene sulfonic acid / styrene sulfonate anion copolymer, etc.
[0064] In one embodiment, the antistatic agent may include a conductive polymer, and the antistatic agent may be a conductive polymer. In the present invention, when the total solid content of the antistatic agent and the thermosetting binder resin is set to 100% by mass, the antistatic agent, such as the conductive polymer, contained in the antistatic layer is preferably contained at 5% by mass or more, more preferably at 10% by mass or more.
[0065] It should be noted that, when using π electron conjugated conductive polymer as an antistatic agent, when using the above-mentioned dopant, the content of the π electron conjugated conductive polymer specified in the present application in the antistatic layer is the total amount of the conductive polymer and the above-mentioned dopant. By containing the antistatic agent in such an amount, good antistatic properties can be imparted. In addition, by adding such an amount, a plurality of tiny concave-convex surfaces from the antistatic agent are formed, and the pressure applied to the particles from the antistatic agent is dispersed, which can suppress the falling off of the antistatic agent, and is therefore preferred.
[0066] In the present invention, the antistatic agent, such as the conductive polymer, contained in the antistatic layer is preferably 60% by mass or less, and more preferably 50% by mass or less, relative to 100% by mass of the total solid content in the antistatic layer. It should be noted that when a π-electron conjugated conductive polymer is used as the antistatic agent, when the above-mentioned dopant is used, the content of the π-electron conjugated conductive polymer in the antistatic layer specified in this application is the total amount of the conductive polymer and the above-mentioned dopant.
[0067] By including the antistatic agent in such an amount, it is preferred because the antistatic agent does not interact with the thermosetting binder resin and the like, and coarse aggregation of particles derived from the antistatic agent is less likely to occur, thereby suppressing the antistatic layer from falling off.
[0068] For example, the antistatic agent may be contained in an amount of 5 mass % to 60 mass % or more, or 10 mass % to 50 mass % or less, based on 100 mass % of the total solid content of the antistatic agent and the thermosetting binder resin.
[0069] In one embodiment, the antistatic agent is contained in an amount of 10% by mass or more and less than 50% by mass, or in an amount of 10% by mass or more and less than 45% by mass. By making the content of the antistatic agent less than 50% by mass, the maximum protrusion height P (also referred to as the maximum peak height P) of the antistatic layer can be further reduced, thereby suppressing the powdering property of the antistatic layer.
[0070] (Thermosetting binder resin)
[0071] The present invention provides an antistatic layer on one surface of the substrate via the first functional layer. The adhesion between the substrate, the first functional layer and the antistatic layer is improved, and as a result, the adhesion between the antistatic layer and the substrate is improved. By improving the adhesion, for example, it is also possible to suppress the detachment of the antistatic layer that may occur due to contact with a guide roller during the molding of the ceramic green sheet. Therefore, it is also possible to suppress the generation of foreign matter during the molding of the ceramic green sheet.
[0072] Furthermore, for example, the film is suitable for long-term storage in a rolled state, and the antistatic layer can be prevented from falling off from the film.
[0073] Thus, the present invention can provide a release film having an antistatic layer that is difficult to come off even by external factors such as friction.
[0074] In the present invention, in order to make the antistatic layer close to the substrate, the antistatic layer is preferably formed by a composition comprising a thermosetting binder resin. By containing a thermosetting binder resin, durability is improved, and even when processed under high temperature and high humidity conditions, the reduction of antistatic performance can be suppressed, so it is preferred. As specific thermosetting binder resins, acrylamide, melamine, carbodiimide, and oxazoline can be listed.
[0075] In one embodiment, the thermosetting binder resin includes at least one selected from the group consisting of acrylamide resin, melamine resin, polycarbodiimide resin, and oxazoline resin.
[0076] From the viewpoint of being able to fully self-crosslink, melamine is preferred. In addition to the thermosetting binder resins described above, there is no particular problem even if urea, epoxy, isocyanate, polycarbodiimide, and aziridine resins are used in combination. In addition, in order to promote the crosslinking reaction, catalysts etc. can be appropriately used as needed.
[0077] In the present invention, it is desirable that the first functional layer contains the components described below. In this case, the present invention can fully exert the functions of each layer by selecting the components described in this specification according to the functions of each layer. Furthermore, a release film having antistatic properties, slippery properties, and adhesion, and having excellent antistatic properties and slippery properties after long-term storage, and an antistatic layer that is difficult to fall off during friction can be provided.
[0078] Examples of the melamine-based thermosetting binder resin used in the present invention include full ether melamine resins, methylol melamine resins, imino melamine resins, and imino / methylol melamine resins.
[0079] There is no particular limitation on the type of these melamine resins, but all-ether melamine resins are most preferred from the viewpoint of curability of the coating film.
[0080] The content of the thermosetting binder resin contained in the antistatic layer of the present invention is 40 mass % to 95 mass % when the total solid content of the conductive polymer and the thermosetting binder resin is 100 mass %.
[0081] Relative to the total solid content 100 mass % in the antistatic layer, the thermosetting binder resin is more preferably 50 mass % or more. If it is 40 mass % or more, a firm coating film with a higher crosslinking density can be obtained, and the adhesion and solvent resistance of the slippery coating layer are good, so it is preferred. And then, if it is 50 mass % or more, it becomes a firmer coating film, so the antistatic performance, sliding property, etc. over time also become good, so it is preferred.
[0082] The thermosetting binder resin is preferably contained in an amount of 95% by mass or less, and may be contained in an amount of 90% by mass or less, relative to 100% by mass of the total solid content in the antistatic layer. If it is contained in an amount of 95% by mass or less, it can be used without affecting the antistatic performance, which is preferred.
[0083] In order to improve the appearance, a surfactant can be used in the antistatic layer of the present invention. As the surfactant, for example, nonionic surfactants such as acetylenic glycol, polyoxyethylene octylphenyl ether, polyoxyethylene alkyl ether, polyoxyethylene sorbitan fatty acid ester, and fluorine-based surfactants such as fluoroalkyl carboxylic acid, perfluoroalkyl carboxylic acid, perfluoroalkyl benzene sulfonic acid, perfluoroalkyl quaternary ammonium, perfluoroalkyl polyoxyethylene ethanol, and silicone-based surfactants can be used.
[0084] In addition to the above, the antistatic layer may contain a lubricant, a pigment, an ultraviolet absorber, a silane coupling agent, and the like as necessary within a range not hindering the purpose of the present invention.
[0085] The film thickness of the antistatic layer of the present invention is preferably 0.005 μm or more and 1 μm or less. It is more preferably 0.01 μm or more and 0.5 μm or less, and further preferably 0.01 μm or more and 0.2 μm or less. When the film thickness of the antistatic layer is 0.005 μm or more, an antistatic effect can be obtained, so it is preferred. On the other hand, when it is 1 μm or less, coloring is less and transparency becomes higher, so it is preferred.
[0086] The surface resistivity of the antistatic layer of the present invention is 10 [logΩ / □] or less. It is further preferably 9 [logΩ / □] or less, and further preferably 8 [logΩ / □] or less. For example, it can be 6.0 [logΩ / □] or less. By making the surface resistivity 10 [logΩ / □] or less, it is possible to suppress the charging of the film and prevent the attachment of foreign matter in the process. Furthermore, by reducing it to 9 [logΩ / □] or less, or 8 [logΩ / □] or less, it is possible to reduce product defects caused by charging during the manufacture of ceramic green sheets, which is preferred.
[0087] The lower limit of the surface resistivity of the antistatic film is not particularly limited, but is preferably 3.0 [logΩ / □] or more. If the surface resistivity of the antistatic film is 3.0 [logΩ / □] or more, the antistatic agent can be used without being transferred to the ceramic green sheet, which is preferred.
[0088] In one embodiment, the surface resistivity of the antistatic film may be 3.2 [logΩ / □] or more, for example, 3.5 [logΩ / □] or more.
[0089] For example, the surface resistivity of the antistatic film is 3.0 [logΩ / □] or more and 8 [logΩ / □] or less.
[0090] In the present invention, the method for forming the antistatic layer is not particularly limited, and the following method can be used: a coating liquid in which the above-mentioned antistatic agent and thermosetting binder resin are dissolved or dispersed is spread on one side of the polyester film of the substrate through the first functional layer described later by coating, etc., and after removing the solvent by drying, etc., heating and drying and heat curing are performed. At this time, the drying temperature during solvent drying and heat curing is preferably below 180°C, and more preferably below 150°C. The heating time is preferably below 30 seconds, and more preferably below 20 seconds. When it is below 180°C, the planarity of the film is maintained, and the possibility of causing uneven thickness of the ceramic raw sheet is small, so it is preferred. If it is below 150°C, it can be processed without damaging the planarity of the film, and the possibility of causing uneven thickness of the ceramic raw sheet is further reduced, so it is particularly preferred.
[0091] (1st functional layer)
[0092] The first functional layer is arranged between the substrate and the antistatic layer. It is particularly arranged to improve the adhesion between the substrate and the antistatic layer. In addition, the first functional layer can help solve the problems in the antistatic layer. For example, the existing antistatic layer is difficult to slide on its surface, so there is a problem that the antistatic layer is easy to fall off due to contact with guide rollers during the molding of the ceramic green sheet. In addition, there is a problem that foreign matter may be generated. The first functional layer in the present invention can help solve the above-mentioned problems of the previous antistatic layer.
[0093] Thus, the first functional layer in the present invention is preferably a layer capable of improving the adhesion between the substrate and the antistatic layer and providing slipperiness to the antistatic layer. In the present invention, the first functional layer that performs this function is referred to as an easy-slip coating layer.
[0094] (Easy-slip coating layer)
[0095] The antistatic release film of the present invention preferably has a slippery coating layer on one surface of the polyester base film as described above. That is, the antistatic layer is provided on one surface of the base film via the slippery coating layer.
[0096] The provision of the easy-slip coating layer not only has the effect of improving the transportability of the film but also improves the adhesion between the substrate and the antistatic layer.
[0097] The easy-slip coating layer preferably contains at least a binder resin and particles.
[0098] (Binder resin in the slippery coating layer)
[0099] As the binder resin constituting the easy-slip coating layer in the present invention, it is preferred to include an acrylic resin. The acrylic resin is preferably an acrylic resin having a hydroxyl group and a carboxyl group in the molecule. The structural unit having a hydroxyl group further preferably contains 20 to 90 mol% in 100 mol% of all structural units. When the structural unit having a hydroxyl group is 20 mol% or more, the water solubility of the acrylic resin can be appropriately maintained, so it is preferred. On the other hand, if it is 90 mol% or less, the hydroxyl group of the acrylic resin and the particles contained in the easy-slip coating layer will not cause extreme interaction, and the particles are uniformly dispersed, so it is preferred.
[0100] In order to introduce hydroxyl groups into acrylic resins, monomers having hydroxyl groups such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, γ-butyrolactone, and ring-opening adducts of ε-caprolactone to 2-hydroxyethyl (meth)acrylate can be used as copolymerization components. Among them, 2-hydroxyethyl (meth)acrylate is preferred from the aspect of not hindering water solubility. It should be noted that they can be used in combination of two or more. Of course, the acrylic resins mentioned in the present invention include methacrylic resins.
[0101] The hydroxyl value of acrylic resin is preferably more than 10mgKOH / g, more preferably more than 20mgKOH / g, and further preferably more than 30mgKOH / g. If the hydroxyl value of acrylic resin is more than 10mgKOH / g, the water solubility of acrylic resin becomes good, so it is preferred. In addition, the reaction site with the thermosetting binder resin in the antistatic layer increases, and the antistatic layer can be more firmly fixed to the substrate, so it is preferred.
[0102] The hydroxyl value of the acrylic resin is preferably 250 mgKOH / g or less, more preferably 230 mgKOH / g or less, and further preferably 200 mgKOH / g or less. If the hydroxyl value of the acrylic resin is 250 mgKOH / g or less, the hydroxyl groups of the acrylic resin and the particles contained in the easy-slip coating layer will not interact extremely, and the particles will be uniformly dispersed, which is preferred.
[0103] The acrylic resin used in the present invention is preferably a resin having a carboxyl group in addition to a hydroxyl group. By having a carboxyl group, a cross-linked structure with a cross-linking agent can be formed, and water solubility can be easily imparted. As examples, monomers containing carboxyl groups such as (meth) acrylic acid, crotonic acid, itaconic acid, maleic acid, and fumaric acid, and monomers containing anhydride groups such as maleic anhydride and itaconic anhydride can be cited.
[0104] The monomer having a carboxyl group is preferably 4 mol% or more, more preferably 10 mol% or more in 100 mol% of all structural units of the acrylic resin. If it is 4 mol% or more, it becomes easy to form a cross-linked structure in the slippery coating layer and impart water solubility, so it is preferred. The monomer having a carboxyl group is preferably 65 mol% or less, more preferably 50 mol% or less. If it is 65 mol% or less, the Tg of the resulting coating film will not become too high relative to the preferred range described later, and the film-forming property and the stretching adaptability in the online coating are good, so it is preferred.
[0105] In order to show good water solubility, it is preferred to neutralize the carboxyl group introduced into the acrylic resin by copolymerization of acrylic acid and methacrylic acid. As alkaline neutralizers, there are inorganic alkaline substances such as ammonia, trimethylamine, triethylamine, dimethylaminoethanol, potassium hydroxide, sodium hydroxide, etc., wherein, for the volatilization ease of the neutralizer and the ease of forming a cross-linked structure, it is preferred to use an amine compound as a neutralizer. Among them, from the viewpoint of no aggregation of particles, ammonia is most preferred. In addition, as a neutralization rate, it is preferably 30 mol% to 95 mol%, more preferably 40 mol% to 90 mol%. If the neutralization rate is 30 mol% or more, the water solubility of the acrylic resin is sufficient, the acrylic resin is easily dissolved when preparing the coating solution, and there is no worry about whitening on the coating surface after drying, so it is preferred. On the other hand, when the neutralization rate is below 95 mol%, the water solubility will not be too high, and the mixing of alcohols and the like in the preparation of the coating solution becomes easy, so it is preferred.
[0106] The acid value of the acrylic resin is preferably 40 mgKOH / g or more, more preferably 50 mgKOH / g or more, and further preferably 60 mgKOH / g or more. If the acid value of the acrylic resin is 40 mgKOH / g or more, the crosslinking points with the oxazoline crosslinking agent or the carbodiimide crosslinking agent increase, so a strong coating film with a higher crosslinking density can be obtained, which is preferred.
[0107] The acid value of the acrylic resin is preferably 400 mgKOH / g or less, more preferably 350 mgKOH / g or less, and further preferably 300 mgKOH / g or less. If the acid value of the acrylic resin is 400 mgKOH / g or less, the carboxyl groups of the acrylic resin and the particles contained in the slippery coating layer will not cause extreme interactions, and the particles are uniformly dispersed, so it is preferred. When the dispersibility of the particles is good, no coarse protrusions are generated on the slippery coating surface, and no pinholes of the ceramic sheet are generated, so it is preferred.
[0108] The glass transition temperature (Tg) of the acrylic resin is preferably 50° C. or higher, more preferably 55° C. or higher, and further preferably 60° C. or higher. When the glass transition temperature of the acrylic resin is 50° C. or higher, the hardness of the easy-slip coating layer becomes appropriately high, which is preferred.
[0109] The glass transition temperature (Tg) of the acrylic resin is preferably 110° C. or lower, more preferably 105° C. or lower, and further preferably 100° C. or lower. If the glass transition temperature of the acrylic resin is 110° C. or lower, the coating film is preferably stretched uniformly without cracking in the stretching step after the easy-slip coating layer is applied.
[0110] As the Tg adjusting monomers copolymerized to make Tg within the above range, (meth)acrylic monomers and non-acrylic vinyl monomers can be used. Specific examples of (meth)acrylic monomers include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and stearyl (meth)acrylate; nitrogen-containing acrylic monomers such as (meth)acrylamide, diacetone acrylamide, n-hydroxymethyl acrylamide, and (meth)acrylonitrile; and vinyl methacrylate, and one or more of them can be used.
[0111] In addition, as non-acrylic vinyl monomers, there can be listed styrene monomers such as styrene, α-methylstyrene, vinyltoluene (a mixture of m-methylstyrene and p-methylstyrene), and chlorostyrene; vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristic acid, vinyl palmitate, vinyl stearate, vinyl cyclohexanecarboxylate, vinyl pivalate, vinyl caprylate, vinyl monochloroacetate, divinyl adipate, vinyl crotonate, vinyl sorbate, vinyl benzoate, and vinyl cinnamate; halogenated vinyl monomers such as vinyl chloride and vinylidene chloride, and one or more of them can be used.
[0112] The monomer for adjusting Tg is preferably used as the remainder after determining the appropriate amounts of the hydroxyl group-containing monomer and the carboxyl group-containing monomer. The Tg of the copolymer is determined by the following Fox equation.
[0113]
[0114] W n : Mass fraction of each monomer (mass %)
[0115] Tg n : Tg(K) of the homopolymer of each monomer
[0116] As the monomers copolymerized for adjusting Tg, it is preferred to introduce a component such as a long-chain alkyl group that reduces the surface free energy. As the acrylic resin into which the long-chain alkyl group is introduced, it is preferred that the acrylic resin has an alkyl group with a carbon number of about 8 to 20 in the side chain of the acrylic resin. In addition, it is also preferred to use a copolymer of a polymer having a (meth)acrylate as a main repeating unit and containing a long-chain alkyl group with a carbon number of 8 to 20 in the part subjected to ester exchange.
[0117] The monomer having a long-chain alkyl group in the monomer copolymerized for Tg adjustment is preferably 50 mol% or less, more preferably 40 mol% or less in 100 mol% of all structural units of the acrylic resin. If it is 50 mol% or less, the Tg of the obtained coating film will not become too low relative to the appropriate range, and the hardness of the coating film can be maintained at a high level, so it is preferred. In the present invention, as long as Tg can be maintained in the appropriate range, the monomer having a long-chain alkyl group can be 0 mol%, but when it is 5 mol% or more, the effect of Tg adjustment of the acrylic resin becomes obvious, so it is preferred.
[0118] The acrylic resin used in the present invention can be obtained by known free radical polymerization. Emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, etc. can all be adopted. From the viewpoint of operability, solution polymerization is preferred. As water-soluble organic solvents that can be used for solution polymerization, ethylene glycol n-butyl ether, isopropyl alcohol, ethanol, n-methyl pyrrolidone, tetrahydrofuran, 1,4-dioxane, 1,3-oxacyclopentane, methyl cellosolve, ethyl cellosolve, ethyl carbitol, butyl carbitol, propylene glycol monopropyl ether, propylene glycol monobutyl ether, etc. can be listed. They can be mixed with water for use.
[0119] The polymerization initiator may be any known compound that generates free radicals, and water-soluble azo polymerization initiators such as 2,2-azobis-2-methyl-N-2-hydroxyethylpropionamide are preferred. The polymerization temperature, time, etc. are appropriately selected.
[0120] The mass average molecular weight (Mw) of the acrylic resin is preferably about 10,000 to 200,000. A more preferred range is 20,000 to 150,000. When Mw is 10,000 or more, there is no concern about thermal decomposition in the tenter, so it is preferred. If Mw is 200,000 or less, the viscosity of the coating liquid does not increase significantly, and the coating property is good, so it is preferred.
[0121] As the binder of the easy-slip coating layer in the present invention, in addition to acrylic resins, other binder resins may be used in combination. Other binder resins include polyester resins, polyurethane resins, polyvinyl resins (polyvinyl alcohol, etc.), polyalkylene glycols, polyalkylene imines, methyl cellulose, hydroxy cellulose, starches, etc.
[0122] The content of acrylic resin in the slippery coating layer is preferably 20% by mass or more and 95% by mass or less in the total solid content. More preferably, it is 30% by mass or more and 90% by mass or less. If it is 20% by mass or more, the carboxyl group as a cross-linking component will not become too small, and the cross-linking density will not decrease, so it is preferred. If it is 95% by mass or less, the amount of the cross-linking agent as a cross-linking object will not become too small, and the cross-linking density will not decrease, so it is preferred.
[0123] (Crosslinking agent)
[0124] In the present invention, in order to form a crosslinked structure in the slippery coating layer, it is preferred that the slippery coating layer contains at least one crosslinking agent selected from oxazoline crosslinking agent or carbodiimide crosslinking agent. By containing oxazoline crosslinking agent or carbodiimide crosslinking agent, the adhesion with the PET substrate can be improved, and the crosslinking with the carboxyl of acrylic resin can be promoted, so that the film strength of the slippery layer can be improved. And then, by selecting the crosslinking agent reacting with the carboxyl group, the hydroxyl in the acrylic resin can be made to remain, and by the reaction of the residual hydroxyl with the thermosetting adhesive in the antistatic layer, more firm adhesion can be given. In addition, other crosslinking agents can also be used in combination, as the specific crosslinking agent that can be used in combination, urea system, epoxy system, melamine system, isocyanate system, silanol system etc. can be listed. In addition, in order to promote the crosslinking reaction, catalyst etc. can be appropriately used as needed.
[0125] Examples of the crosslinking agent having an oxazoline group include polymers having an oxazoline group obtained by copolymerizing a polymerizable unsaturated monomer having an oxazoline group and, if necessary, other polymerizable unsaturated monomers by a conventionally known method (eg, solution polymerization, emulsion polymerization, etc.).
[0126] As the polymerizable unsaturated monomer with oxazoline group, for example, 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline etc. can be listed. They can be used alone, and two or more kinds can also be used in combination.
[0127] Examples of other polymerizable unsaturated monomers include alkyl or cycloalkyl (meth)acrylates having 1 to 24 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, and isobornyl (meth)acrylate; hydroxyalkyl (meth)acrylates having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate; vinyl aromatic compounds such as styrene and vinyltoluene; (meth)acrylamide, dimethylaminopropyl (meth)acrylamide, dimethylaminoethyl (meth)acrylate, and adducts of glycidyl (meth)acrylate and amines; polyethylene glycol (meth)acrylate; N-vinyl pyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, vinyl acetate, and (meth)acrylonitrile. These monomers may be used alone or in combination of two or more.
[0128] From the viewpoint of improving the compatibility, wettability, crosslinking reaction efficiency, etc. of the crosslinking agent with oxazoline obtained as a water-soluble crosslinking agent with other resins, other polymerizable unsaturated monomers are preferably hydrophilic monomers. As hydrophilic monomers, monomers with polyethylene glycol chains such as (methyl) 2-hydroxyethyl acrylate, methoxypolyethylene glycol (methyl) acrylate, (methyl) acrylic acid and the monoester compound of polyethylene glycol, (methyl) 2-aminoethyl acrylate and its salt, (methyl) acrylamide, N-hydroxymethyl (methyl) acrylamide, N-(2-hydroxyethyl) (methyl) acrylamide, (methyl) acrylonitrile, sodium styrene sulfonate, etc. can be listed. Among them, monomers with polyethylene glycol chains such as methoxypolyethylene glycol (methyl) acrylate, (methyl) acrylic acid and the monoester compound of polyethylene glycol with high solubility in water are preferred.
[0129] The content of the oxazoline group in the cross-linking agent having an oxazoline group is preferably 3.0 to 9.0 mmol / g, more preferably 4.0 to 8.0 mmol / g. If it is within the range of 4.0 to 8.0 mmol / g, a moderate cross-linking structure can be formed, which is preferred.
[0130] As the carbodiimide crosslinking agent, monocarbodiimide compounds and polycarbodiimide compounds can be listed. As the monocarbodiimide compound, for example, dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, diphenylcarbodiimide, di-tert-butylcarbodiimide, di-β-naphthylcarbodiimide etc. can be listed. As the polycarbodiimide compound, the polycarbodiimide compound manufactured by the conventionally known method can be used. For example, isocyanate-terminated polycarbodiimide can be synthesized by the condensation reaction of decarbonation of diisocyanate to manufacture.
[0131] Diisocyanates as a synthetic raw material of the polycarbodiimide compound include, for example, isomers of toluene diisocyanate, aromatic diisocyanates such as 4,4-diphenylmethane diisocyanate, aromatic aliphatic diisocyanates such as xylylene diisocyanate, alicyclic diisocyanates such as isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate. In view of the problem of yellowing, aromatic aliphatic diisocyanates, alicyclic diisocyanates, and aliphatic diisocyanates are preferred.
[0132] In addition, the above-mentioned diisocyanate can also be used by controlling the molecule to an appropriate degree of polymerization by using a compound that reacts with a terminal isocyanate, such as a monoisocyanate. As such a monoisocyanate for controlling the degree of polymerization by blocking the end of the polycarbodiimide, for example, phenyl isocyanate, toluene isocyanate, dimethylphenyl isocyanate, cyclohexyl isocyanate, butyl isocyanate, naphthyl isocyanate, etc. can be cited. In addition, as an end-capping agent, a compound having an OH group, -NH2 group, COOH group, SO3H group can be used.
[0133] The condensation reaction of the decarbonation of diisocyanate is carried out in the presence of a carbodiimidization catalyst. As catalyst, for example, 1-phenyl-2-phosphole-1-oxide, 3-methyl-2-phosphole-1-oxide, 1-ethyl-2-phosphole-1-oxide, 3-methyl-1-phenyl-2-phosphole-1-oxide, their 3-phosphole isomers and other phosphole oxides etc. can be listed, from the aspect of reactivity, preferably 3-methyl-1-phenyl-2-phosphole-1-oxide. It should be noted that the usage amount of the above-mentioned catalyst can be set as catalyst amount.
[0134] The above-mentioned monocarbodiimide compound or polycarbodiimide compound is expected to maintain a uniform dispersion state when mixed into an aqueous coating, and therefore it is preferably emulsified using a suitable emulsifier and used as an emulsion, or a hydrophilic segment is added to the molecular structure of the polycarbodiimide compound and mixed into the coating in the form of a self-emulsifiable product or a self-dissolving product.
[0135] The carbodiimide crosslinking agent used in the present invention can be water dispersible or water soluble. Water soluble is preferred from the perspective of good compatibility with other water soluble resins and improved crosslinking reaction efficiency of the slippery coating layer. In order to make the carbodiimide compound water soluble, it can be prepared by synthesizing an isocyanate-terminated polycarbodiimide through a condensation reaction accompanied by decarbonation of an isocyanate, and then further adding a hydrophilic part having a functional group reactive with an isocyanate group.
[0136] Examples of the hydrophilic part include: (1) quaternary ammonium salts of dialkylamino alcohols, quaternary ammonium salts of dialkylaminoalkylamines, etc.; (2) alkyl sulfonates having at least one reactive hydroxyl group, etc.; (3) poly(ethylene oxide) terminated with an alkoxy group, a mixture of poly(ethylene oxide) and poly(propylene oxide), etc. When the above hydrophilic part is introduced, the carbodiimide compound becomes (1) cationic, (2) anionic, or (3) nonionic. Among them, nonionic compounds that are compatible with other water-soluble resins are preferred regardless of their ionicity.
[0137] The content of the crosslinking agent in the slippery coating layer is preferably 5% by mass or more and 80% by mass or less in the total solid content. More preferably, it is 10% by mass or more and 70% by mass or less. If it is 5% by mass or more, the crosslinking density of the resin in the coating layer will not decrease, so it is preferred. If it is 80% by mass or less, the amount of carboxyl groups in the acrylic resin to be crosslinked will not become too small, and the crosslinking density will not decrease, so it is preferred.
[0138] (Particles in the slippery coating layer)
[0139] In order to impart slip properties to the surface, the slippery coating layer preferably contains lubricant particles. The particles may be inorganic particles or organic particles, and are not particularly limited, and examples thereof include: (1) inorganic particles such as silicon dioxide, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, aluminum oxide, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, zirconium oxide, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, halloysite, calcium carbonate, magnesium carbonate, calcium phosphate, magnesium hydroxide, and barium sulfate; (2) organic particles such as acrylic acid or methacrylic acid series, vinyl chloride series, vinyl acetate series, nylon, styrene / acrylic acid series, styrene / butadiene series, polystyrene / acrylic acid series, polystyrene / isoprene series, polystyrene / isoprene series, methyl methacrylate / butyl methacrylate series, melamine series, polycarbonate series, urea series, epoxy series, urethane series, phenol series, diallyl phthalate series, and polyester series.
[0140] From the perspective of preventing particles from falling off from the slippery coating layer, it is particularly preferred to use organic particles. By using organic particles, the interaction with the binder and crosslinking agent components of the slippery coating layer becomes stronger, and it becomes easier to prevent falling off, so it is preferred. In terms of the prevention of particles from falling off from the slippery coating layer, acrylic resin particles and / or methacrylic resin particles having a chemical structure similar to that of the acrylic resin present in the slippery coating layer are particularly preferred among the organic particles.
[0141] The average particle size of the particles is preferably 10 nm or more, more preferably 20 nm or more, and further preferably 30 nm or more. When the average particle size of the particles is 10 nm or more, the particles are less likely to aggregate and the sliding property can be ensured, which is preferred.
[0142] The average particle size of the particles is preferably 1000 nm or less, more preferably 800 nm or less, and further preferably 600 nm or less. When the average particle size of the particles is 1000 nm or less, transparency can be maintained and the particles will not fall off, which is preferred.
[0143] In addition, for example, small particles with an average particle size of about 10 to 270 nm and large particles with an average particle size of about 300 to 1000 nm are mixed, and while keeping the average surface roughness (Sa) and the maximum protrusion height (P) of the region described later small, the average length (RSm) of the roughness curve element is reduced, and it is also preferred to take into account both sliding and smoothness. It is particularly preferred to use a combination of small particles of more than 30 nm and less than 250 nm and large particles with an average particle size of 350 to 600 nm. In the case of mixing small particles and large particles, it is preferred to make the mass content of small particles greater than the mass content of large particles relative to the entire solid component of the coating layer.
[0144] The average particle size of the particles is measured by observing the particles in the cross section of the processed film with a transmission electron microscope or a scanning electron microscope, observing 100 unaggregated particles, and taking the average value thereof as the average particle size.
[0145] As long as the purpose of the present invention is met, the shape of the particles is not particularly limited, and spherical particles and amorphous non-spherical particles can be used. The particle size of the amorphous particles can be calculated as the equivalent circle diameter. The equivalent circle diameter is the value obtained by dividing the area of the observed particles by π, calculating the square root and multiplying by 2.
[0146] The ratio of the particles to the total solid content of the easy-slip coating layer is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less. If the ratio of the particles to the total solid content of the easy-slip coating layer is 50% by mass or less, transparency can be maintained and particles will not significantly fall off from the easy-slip coating layer, which is preferred.
[0147] The ratio of the particles to the total solid content of the easy-slip coating layer is preferably 1% by mass or more, more preferably 1.5% by mass or more, and further preferably 2% by mass or more. If the ratio of the particles to the total solid content of the easy-slip coating layer is 1% by mass or more, it is preferred because sliding properties can be ensured.
[0148] As a method for determining the content of particles contained in the slippery coating layer, for example, in the case of a resin and inorganic particles containing an organic component in the slippery coating layer, the following method can be used. First, the slippery coating layer provided on the processed film is extracted from the processed film using a solvent or the like and dried to thereby take out the slippery coating layer. Next, heat is applied to the obtained slippery coating layer, and the organic components contained in the slippery coating layer are burned and distilled off by heat, thereby obtaining only the inorganic components. By measuring the weight of the obtained inorganic component and the slippery coating layer before burning and distilling off, the mass % of the particles contained in the slippery coating layer can be determined. At this time, by using a commercially available differential thermal / thermogravimetric simultaneous determination device, it is possible to measure with high precision. It should be noted that the ratio of the above-mentioned particles in the total solid content of the slippery coating layer refers to the ratio of the total amount of the multiple particles when there are multiple particles.
[0149] (Additives in slippery coatings)
[0150] In order to impart other functionalities to the slippery coating layer, various additives may be contained within a range that does not impair the coating appearance. Examples of the additives include fluorescent dyes, fluorescent brighteners, plasticizers, ultraviolet absorbers, pigment dispersants, foam suppressants, defoamers, preservatives, and the like.
[0151] The slippery coating layer may also contain a surfactant for the purpose of improving the leveling property during coating and degassing the coating solution. The surfactant may be any surfactant such as a cationic, anionic, or nonionic surfactant, preferably a silicone, acetylene glycol, or fluorine-based surfactant. These surfactants are preferably contained in the coating layer to a degree that does not cause abnormal coating appearance due to excessive addition.
[0152] As the coating method, both the so-called in-line coating method in which the polyester base film is coated simultaneously with the film formation and the so-called off-line coating method in which the polyester base film is coated with a separate coater after the film formation can be applied. However, the in-line coating method is more effective and therefore more preferred.
[0153] As a coating method, any known method can be used for coating the coating liquid on the polyethylene terephthalate (hereinafter, sometimes referred to as PET) film. For example, reverse coating, gravure coating, kiss coating, die coating, roller brushing, spraying, air knife coating, wire rod coating, tubular doctor blade, dip coating, curtain coating, etc. can be listed. These methods can be used alone or in combination for coating.
[0154] In the present invention, as a method for providing a slippery coating layer on a polyester film, there can be cited a method of applying a coating liquid containing a solvent, particles, and a resin to a polyester film and drying the coating liquid. As the solvent, there can be cited an organic solvent such as toluene, water, or a mixed system of water and a water-soluble organic solvent. From the perspective of environmental issues, it is preferred to use water alone or a so-called aqueous solvent obtained by mixing a water-soluble organic solvent with water.
[0155] The solid content concentration of the easy-slip coating liquid also depends on the type of binder resin, the type of solvent, etc., but is preferably 0.5% by mass or more, more preferably 1% by mass or more. The solid content concentration of the coating liquid is preferably 35% by mass or less, more preferably 20% by mass or less.
[0156] The drying temperature after coating depends on the type of binder resin, the type of solvent, the presence or absence of a crosslinking agent, the solid content concentration, etc., but is preferably 70° C. or higher and preferably 250° C. or lower.
[0157] (Manufacture of polyester film)
[0158] In the present invention, the polyester film as the substrate film can be produced according to a conventional polyester film production method. For example, the following method can be cited: the polyester resin is melted, and the non-oriented polyester extruded into a sheet is stretched longitudinally at a temperature above the glass transition temperature by using a roller speed difference, and then stretched transversely by using a tenter, and heat-treated. In addition, a method of performing biaxial stretching in the longitudinal and transverse directions simultaneously in a tenter can also be cited.
[0159] In the present invention, the polyester film as the substrate film may be a uniaxially stretched film or a biaxially stretched film, and is preferably a biaxially stretched film.
[0160] The thickness of the polyester film substrate is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 15 μm or more. A thickness of 5 μm or more is preferred because wrinkles are less likely to occur during transport of the film.
[0161] The thickness of the polyester film substrate is preferably 50 μm or less, more preferably 45 μm or less, and even more preferably 40 μm or less. A thickness of 40 μm or less is preferred because the cost per unit area is reduced.
[0162] In the case of online coating, it can be coated on an unstretched film before longitudinal stretching, or it can be coated on a uniaxially stretched film after longitudinal stretching and before transverse stretching. In the case of coating before longitudinal stretching, it is preferred to set a drying process before roller stretching. In the case of coating a uniaxially stretched film before transverse stretching, the film heating process in the tenter can be used as a drying process, so it is not necessarily necessary to set a drying process separately. It should be noted that the same is true for the case of simultaneous biaxial stretching.
[0163] The thickness of the slippery coating layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, further preferably 0.02 μm or more, and particularly preferably 0.03 μm or more. A coating layer thickness of 0.001 μm or more is preferred because the film-forming property of the coating film can be maintained and a uniform coating film can be obtained.
[0164] The thickness of the easy-slip coating layer is preferably 2 μm or less, more preferably 1 μm or less, further preferably 0.8 μm or less, and particularly preferably 0.5 μm or less. If the thickness of the coating layer is 2 μm or less, there is no concern of blocking, which is preferred.
[0165] The ceramic green sheet coated and formed on the release layer described later is wound into a roll together with the release film after coating and forming. At this time, the back of the release film is wound in contact with the surface of the ceramic green sheet. In order to prevent defects from occurring on the surface of the ceramic green sheet, the outermost surface of the release film (the outermost surface of the entire release layer that is not in contact with the polyester film) needs to be moderately flat.
[0166] The average surface roughness (Sa) of the region on the opposite side to the substrate in the release layer is 0.1 nm to 5 nm, for example, 0.2 nm to 4.5 nm.
[0167] The maximum protrusion height (P) is preferably greater than or equal to 1 nm and less than or equal to 50 nm, for example, greater than or equal to 1 nm and less than or equal to 40 nm.
[0168] The average surface roughness (Sa) of the region on the opposite side of the antistatic layer to the substrate is 1 nm or more and 25 nm or less, and the maximum protrusion height (P) is 60 nm or more and 500 nm or less. By making the average roughness (Sa) and the maximum protrusion height (P) in such a range, the slippery coating surface will not be too smooth, and it is possible to maintain moderate sliding properties, so it is preferred. Furthermore, the slippery coating surface will not be too rough, and defects of the ceramic green sheet caused by the protrusion will not occur, so it is preferred. In one embodiment, the average surface roughness (Sa) of the region is 1 nm or more and 20 nm or less, and the maximum protrusion height (P) is 60 nm or more and 300 nm or less.
[0169] It is desirable that the average surface roughness (Sa) and the maximum protrusion height (P) of the region on the surface opposite to the substrate in the antistatic layer are both greater than the average surface roughness (Sa) and the maximum protrusion height (P) of the region on the surface opposite to the substrate in the release layer. By making the antistatic layer and the release layer have such a relationship, for example, it is suitable for long-term storage and transportation in a rolled state, and it is possible to suppress the antistatic layer from falling off the film.
[0170] (Release layer)
[0171] The release layer is provided on the side of the substrate which is different from the antistatic layer.
[0172] The resin constituting the release layer in the present invention is not particularly limited, and silicone resins, fluororesins, alkyd resins, various waxes, aliphatic olefins and the like can be used. Each resin can be used alone or in combination of two or more.
[0173] As the release layer in the present invention, for example, silicone resin refers to a resin having a silicone structure in the molecule, and examples thereof include curable silicone, silicone grafted resin, alkyl-modified modified silicone resin, etc. From the viewpoint of transferability, etc., it is preferred to use a reactive curable silicone resin. As a reactive curable silicone resin, a curable silicone resin of an addition reaction system, a curable silicone resin of a condensation reaction system, a curable silicone resin of an ultraviolet or electron beam curing system, etc. can be used. More preferably, it can be a curable silicone resin of a low-temperature curable addition reaction system that can be processed at low temperatures, and a curable silicone resin of an ultraviolet or electron beam curing system. By using these silicone resins, when the polyester film is coated, it can be processed at low temperatures. Therefore, a polyester film with less thermal damage to the polyester film during processing and high flatness can be obtained, and defects such as pinholes can also be reduced when manufacturing ultra-thin film ceramic green sheets with a thickness of 0.2 to 2.0 μm.
[0174] Examples of the addition reaction type silicone resin include silicone resins cured by reacting polydimethylsiloxane having a vinyl group introduced at the terminal or side chain with polyorganohydrogensiloxane using a platinum catalyst. In this case, it is more preferable to use a resin that can be cured within 30 seconds at 120° C. because processing at low temperatures is more possible. As examples, there can be listed low-temperature addition curing types (LTC1006L, LTC1056L, LTC300B, LTC303E, LTC310, LTC314, LTC350G, LTC450A, LTC371G, LTC750A, LTC755, LTC760A, etc.) and thermal UV curing types (LTC851, BY24-510, BY24-561, BY24-562, etc.) manufactured by Dow Corning Toray Co., Ltd., solvent addition + UV curing types (X62-5040, X62-5065, X62-5072T, KS5508, etc.), and dual-cure curing types (X62-2835, X62-2834, X62-1980, etc.) manufactured by Shin-Etsu Chemical Co., Ltd.
[0175] Examples of the condensation reaction system silicone resin include silicone resins having a three-dimensional crosslinked structure formed by condensation reaction of polydimethylsiloxane having an OH group at the terminal and polydimethylsiloxane having an H group at the terminal using an organic tin catalyst.
[0176] As the silicone resin of UV curing system, for example, there can be listed silicone resins that use the same free radical reaction as the most basic type of conventional silicone rubber cross-linking, silicone resins that are photocured by introducing unsaturated groups, silicone resins that are cross-linked by cleaving epoxy groups by decomposing onium salts using ultraviolet rays to generate strong acids, and silicone resins that are cross-linked by addition reaction of thiols to vinyl siloxanes. In addition, electron beams can also be used instead of the aforementioned ultraviolet rays. The energy of electron beams is stronger than that of ultraviolet rays, and free radical-based cross-linking reactions can be carried out even without using an initiator as in the case of ultraviolet curing. Examples of the resin used include UV-curing silicones manufactured by Shin-Etsu Chemical Co., Ltd. (X62-7028A / B, X62-7052, X62-7205, X62-7622, X62-7629, X62-7660, etc.), UV-curing silicones manufactured by Momentive Performance Materials Co., Ltd. (TPR6502, TPR6501, TPR6500, UV9300, UV9315, XS56-A2982, UV9430, etc.), and UV-curing silicones manufactured by Arakawa Chemical Co., Ltd. (Silcolease UV POLY200, POLY215, POLY201, KF-UV265AM, etc.).
[0177] As the above-mentioned ultraviolet curing silicone resin, acrylate-modified, glycidoxy-modified polydimethylsiloxane, etc. can also be used. By mixing these modified polydimethylsiloxanes with multifunctional acrylate resins, epoxy resins, etc., and using them in the presence of an initiator, good mold release properties can also be exhibited.
[0178] Examples of other resins that can be used include stearyl-modified, lauryl-modified, or other alkyd resins and acrylic resins, and alkyd resins and acrylic resins obtained by reaction with methylated melamine.
[0179] Examples of the aminoalkyd resin obtained by reaction with methylated melamine include Tesfine 303, Tesfine 305, and Tesfine 314 manufactured by Hitachi Chemical Co., Ltd. Examples of the aminoacrylic resin obtained by reaction with methylated melamine include Tesfine 322 manufactured by Hitachi Chemical Co., Ltd.
[0180] When the above resins are used in the release layer of the present invention, one type may be used or two or more types may be mixed and used. In order to adjust the release force, additives such as a light release additive and a heavy release additive may be mixed.
[0181] The release coating layer in the present invention may contain particles having a particle size of 1 μm or less, but it is more preferable that the release coating layer substantially does not contain particles or other substances forming protrusions from the viewpoint of the formation of pinholes.
[0182] The release layer of the present invention may contain additives such as adhesion improvers and antistatic agents. In addition, in order to improve adhesion to the substrate, it is also preferred to perform pretreatment such as anchor coating, corona treatment, plasma treatment, atmospheric pressure plasma treatment on the surface of the polyester film before providing the release coating layer.
[0183] In the present invention, the thickness of the release layer can be set according to its purpose of use, and there is no particular limitation. The thickness of the release coating layer after curing is preferably in the range of 0.005 to 2.0 μm. When the thickness of the release coating layer is 0.005 μm or more, the peeling performance can be maintained, so it is preferred. In addition, when the thickness of the release coating layer is 2.0 μm or less, the curing time will not become too long, and there is no concern about uneven thickness of the ceramic green sheet caused by the reduction of the planarity of the release film, so it is preferred. In addition, since the curing time will not be too long, the resin constituting the release coating layer will not aggregate and will not form protrusions, so it is difficult to produce pinhole defects in the ceramic green sheet, so it is preferred.
[0184] For the outer surface of the film formed with a release layer (the surface of the release coating layer of the entire coated film that is not in contact with the polyester film), in order to prevent defects in the ceramic green sheet coated and formed thereon, it is desired to be flat, and the regional surface average roughness (Sa) is preferably less than 5nm and the maximum protrusion height (P) is less than 30nm. Furthermore, it is more preferred that the regional surface average roughness is less than 5nm and the maximum protrusion height is less than 20nm. If the regional surface roughness is less than 5nm and the maximum protrusion height is less than 30nm, defects such as pinholes will not be generated when the ceramic green sheet is formed, and the yield is good, so it is preferred. It can be said that the smaller the regional surface average roughness (Sa), the better, but it can be greater than 0.1nm, or it can be greater than 0.3nm. The maximum protrusion height (P) can also be said to be smaller, the better, but it can be greater than 1nm, or it can be greater than 3nm.
[0185] In the present invention, the method for forming the release layer is not particularly limited, and the following method can be used: a coating liquid in which a resin having a release property is dissolved or dispersed is spread on one surface of the polyester film of the substrate by coating, etc., and after removing the solvent by drying, etc., heating and drying, heat curing or ultraviolet curing is performed. At this time, the drying temperature during solvent drying and heat curing is preferably below 180°C, more preferably below 150°C, and most preferably below 120°C. The heating time is preferably below 30 seconds, more preferably below 20 seconds. When it is below 180°C, the planarity of the film is maintained, and the possibility of causing uneven thickness of the ceramic green sheet is small, so it is preferred. If it is below 120°C, it can be processed without damaging the planarity of the film, and the possibility of causing uneven thickness of the ceramic green sheet is further reduced, so it is particularly preferred.
[0186] In the present invention, the surface tension of the coating liquid when applying the release layer forming composition is not particularly limited, but is preferably 30 mN / m or less. By setting the surface tension as described above, the coating properties after coating are improved and the unevenness of the coating film surface after drying can be reduced.
[0187] In the present invention, the coating liquid for applying the composition for forming the release layer is not particularly limited, but preferably a solvent having a boiling point of 90° C. or higher is added. By adding a solvent having a boiling point of 90° C. or higher, sudden boiling during drying can be prevented, the coating film can be leveled, and the smoothness of the coating film surface after drying can be improved. As for the amount of addition, about 10 to 80% by mass is preferably added relative to the entire coating liquid.
[0188] As a coating method for the composition forming the above-mentioned release layer, any known coating method can be applied, for example, a roll coating method such as a gravure coating method, a reverse coating method, a rod coating method such as a wire bar, a die coating method, a spray coating method, an air knife coating method, or the like can be used.
[0189] The release film with an antistatic layer of the present invention is wound on a roll, and the release film roll is stored in an environment of 40°C and a humidity of 50% or less for 30 days, and the charge amount when the film is unwound at 100 m / min is greater than -2 kV and less than +2 kV. In one embodiment, the charge amount is greater than -1.5 kV and less than +1.5 kV, for example, greater than -1.0 kV and less than +1.0 kV.
[0190] In one embodiment, the charge amount is greater than or equal to -0.5 kV and less than or equal to +0.5 kV.
[0191] By setting the charge amount within such a range, it is possible to suppress the inclusion of foreign matter during the production of ceramic green sheets, and to reduce product defects due to charge.
[0192] (Ceramic Green Sheets and Ceramic Capacitors)
[0193] Typically, a multilayer ceramic capacitor has a rectangular ceramic body. Inside the ceramic body, a first internal electrode and a second internal electrode are alternately arranged along the thickness direction. The first internal electrode is exposed at the first end face of the ceramic body. A first external electrode is arranged on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed at the second end face of the ceramic body. A second external electrode is arranged on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.
[0194] The release film for manufacturing ceramic green sheets of the present invention is used to manufacture such a stacked ceramic capacitor. For example, it is manufactured as follows. First, using the release film of the present invention as a carrier film, a ceramic slurry for constituting a ceramic body is applied and dried. A conductive layer for constituting the first or second internal electrode is printed on the coated and dried ceramic green sheet. Ceramic green sheets, ceramic green sheets printed with a conductive layer for constituting the first internal electrode, and ceramic green sheets printed with a conductive layer for constituting the second internal electrode are appropriately stacked and pressed to obtain a mother stack. The mother stack is divided into a plurality of pieces to produce an unprocessed ceramic body. The ceramic body is obtained by firing the unprocessed ceramic body. Thereafter, the first and second external electrodes are formed, thereby completing the stacked ceramic capacitor.
[0195] Example
[0196] Next, the present invention will be described in detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples. In addition, the evaluation method used in the present invention is as follows.
[0197] [NMR measurement]
[0198] The ratio of the copolymerization component introduced into the acrylic polyol can be determined using nuclear magnetic resonance spectroscopy ( 1 H-NMR,13 C-NMR: Varian Unity 400, manufactured by Agilent). After removing the solvent from the synthesized acrylic polyol with a vacuum dryer, the dried solid was dissolved in deuterated chloroform for measurement. The peaks of chemical shift δ (ppm) at the position of each group were identified from the obtained NMR spectrum. The integrated intensity of each obtained peak was calculated, and the composition ratio (mol %) of the copolymer component introduced into the acrylic polyol was confirmed from the number of hydrogen atoms at the position of each group and the integrated intensity.
[0199] [Confirmation of Tg]
[0200] The Tg of the acrylic polyol can be determined from the composition ratio of the copolymer components determined by the NMR measurement and the aforementioned Fox equation.
[0201] (1) Surface properties of coated films
[0202] The values are measured using a non-contact surface topography measurement system (VertScan R550H-M100) under the following conditions. The average values of five measurements are used for the area surface average roughness (Sa) and the average length of the roughness curve element (RSm), and the maximum protrusion height (P) is used for the maximum value of five measurements.
[0203] (Measurement conditions)
[0204] ·Measurement mode: WAVE mode
[0205] Objective lens: 50 times
[0206] 0.5× tube lens
[0207] ·Measurement area 187×139μm (Sa, P measurement)
[0208] (4) Powder shedding resistance of antistatic layer
[0209] A peeling film for green sheet production (3 cm (film width direction) × 20 cm (film length direction)) was installed on a friction fastness tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd.) so that the antistatic layer was on top, and an aluminum foil (thickness 80 μm, arithmetic mean surface roughness 0.03 μm) was used at the contact part between the load head (2 cm × 2 cm, 200 g) and the sample film, and the load head (2 cm × 2 cm, 200 g) was reciprocated 10 times at a speed of 2 seconds per reciprocation at a distance of 10 cm. The obtained film was placed on a black backing paper and visually confirmed whether powdering occurred.
[0210] ◎: No powder loss was observed on the black backing paper.
[0211] ○: Slight powdering was observed on a portion of the black backing paper.
[0212] △: Slight powder loss was observed on the black backing paper as a whole.
[0213] ×: Powder loss was confirmed on the entire black backing paper.
[0214] (5) Surface resistivity measurement
[0215] The surface resistivity of the antistatic film surface of the present invention was measured by using a surface resistivity measuring instrument (manufactured by SIMCO JAPAN, working surface tester ST-3) after humidity adjustment for 24 hours at a temperature of 23° C. and a humidity of 55%, and evaluated according to the following criteria.
[0216] ◎: Surface resistivity is 3 or more and 6 or less [logΩ / □]
[0217] ○: Surface resistivity greater than 6 and less than 10 [logΩ / □]
[0218] △: Surface resistivity greater than 10 and less than 12 [logΩ / □]
[0219] ×: Surface resistivity greater than 12 [logΩ / □]
[0220] (5) Solvent resistance evaluation method A
[0221] The surface of the antistatic layer was rubbed back and forth 10 times using a wiping paper soaked with a solvent (toluene). In addition, the change in appearance after the above treatment was evaluated according to the following criteria.
[0222] 0: Almost no change
[0223] △: There is a change
[0224] ×: The antistatic layer shows a change in the degree of staining and shedding
[0225] (6) Evaluation of solvent resistance Method B
[0226] The surface of the antistatic layer was rubbed back and forth 10 times using a wiping paper soaked with a solvent (ethanol). In addition, the change in appearance after the above treatment was evaluated according to the following criteria.
[0227] 0: Almost no change
[0228] △: There is a change
[0229] ×: The antistatic layer shows a change in the degree of staining and shedding
[0230] (7) Determination of peeling force of ceramic green sheets
[0231] Next, the dried slurry was applied to the release surface of the obtained release film sample using an applicator to a thickness of 2.0 μm, and dried at 60°C for 1 minute to form a ceramic green sheet on the release film. After the obtained release film with the ceramic green sheet was de-electrified using a de-electrifying machine (SJ-F020 manufactured by KEYENCE CORPORATION), it was peeled using a peeling tester (VPA-3 manufactured by Kyowa Interface Science Co., Ltd., load cell load 0.1N) at a peeling angle of 90 degrees, a peeling temperature of 25°C, and a peeling speed of 10 m / min. As the peeling direction, a double-sided adhesive tape (No. 535A manufactured by Nitto Denko Corporation) was attached to the SUS plate attached to the peeling tester, and the release film was fixed thereon in the form of bonding the release film side to the double-sided tape, and peeled in the form of stretching the ceramic green sheet side. From the obtained measured values, the average value of the peeling force at a peeling distance of 20 mm to 70 mm was calculated, and this value was used as the peeling force. The measurement was performed 5 times in total, and the average value of the peeling force was used for evaluation. The obtained peeling force values were judged according to the following criteria.
[0232] ◎: 0.4mN / mm or more and 0.6mN / mm or less
[0233] ○: greater than 0.6 mN / mm and less than 0.8 mN / mm
[0234] △: greater than 0.8mN / mm and less than 1.0mN / mm
[0235] ×: Less than 0.4 mN / mm or greater than 1.0 mN / mm, or the ceramic green sheet was broken during the measurement
[0236] (8) Evaluation of pinholes and thickness deviation of ceramic green sheets
[0237] The antistatic release film obtained in each example and each comparative example was rolled into a roll having a width of 400 mm and a length of 5000 m to obtain an antistatic release film. The antistatic release film roll was stored at 40° C. and a humidity of 50% or less for 30 days and then evaluated.
[0238] The slurry composition I composed of the following materials was stirred and mixed for 10 minutes, and dispersed for 10 minutes using a bead mill with zirconia beads having a diameter of 0.5 mm to obtain a primary dispersion. Then, the slurry composition II composed of the following materials was added to the primary dispersion at a ratio of (slurry composition I): (slurry composition II) = 3.4: 1.0, and dispersed for a second time within 10 minutes using a bead mill with zirconia beads having a diameter of 0.5 mm to obtain a ceramic slurry.
[0239] (Slurry composition I)
[0240] Toluene 22.3 parts by mass
[0241] Ethanol 18.3 parts by mass
[0242] Barium titanate (average particle size 100 nm) 57.5 parts by mass
[0243] HOMOGENOL-18 (manufactured by Kao Corporation) 1.9 parts by mass
[0244] (Slurry composition II)
[0245] Toluene 39.6 parts by mass
[0246] Ethanol 39.6 parts by mass
[0247] Dioctyl phthalate 3.3 parts by mass
[0248] Polyvinyl butyral (S-LEC BM-S manufactured by Sekisui Chemical Co., Ltd.) 16.3 parts by mass
[0249] 1-Ethyl-3-methylimidazolium ethyl sulfate 0.5 parts by mass
[0250] The slurry was applied on the release surface of the antistatic release film sample using an applicator so that the thickness of the dried slurry was 0.5 μm. After drying at 90°C for 1 minute, the slurry surface was overlapped with the smoothed coating surface and applied for 10 minutes at 1 kg / cm 2 After the load is applied, the release film is peeled off to obtain a ceramic green sheet.
[0251] In the central region of the film width direction of the obtained ceramic green sheet, at 25 cm 2 Light was irradiated from the opposite side of the ceramic slurry coating surface within a range of , and the occurrence of pinholes visible through the light was observed, and visual judgment was performed according to the following criteria.
[0252] ◎: No pinholes, excellent thickness variation
[0253] ○: No pinholes, no obvious thickness deviation
[0254] △: Pinholes are rarely generated and slight thickness deviation is observed.
[0255] ×: Pinholes are slightly generated and thickness deviation is slightly noticeable.
[0256] (9) Unwinding of release film rolls is charged
[0257] The antistatic release film obtained in each embodiment and each comparative example was rolled into a roll with a width of 400 mm and a length of 5000 m to obtain an antistatic release film roll. After the antistatic release film roll was stored at 40°C and a humidity of 50% or less for 30 days, the charge amount when unwinding at 100 m / min was measured using "KSD-0103" manufactured by KASUGA DENKI, INC. Regarding the charge amount, the 100 mm portion just unwound was measured every 500 m of the unwinding length, and the average value was calculated.
[0258] ◎: greater than -0.5kV and less than 0.5kV
[0259] ○: 0.5 kV or more and less than 1 kV, or greater than -1 kV and less than -0.5 kV
[0260] △: 1kV or more and less than 5kV, or greater than -5kV and less than -1kV
[0261] ×: -5kV or less, 5kV or more
[0262] (Preparation of polyethylene terephthalate particles (PET (I)))
[0263] As the esterification reaction apparatus, a continuous esterification reaction apparatus consisting of a three-stage complete mixing tank having a stirring device, a partial condenser, a raw material inlet, and a product outlet was used. TPA (terephthalic acid) was set to 2 tons / hour, EG (ethylene glycol) was set to 2 mol per 1 mol of TPA, and antimony trioxide was set to an amount of 160 ppm of Sb atoms per generated PET. These slurries were continuously supplied to the first esterification reaction tank of the esterification reaction apparatus, and the reaction was carried out at 255° C. at an average residence time of 4 hours under normal pressure. Next, the reaction product in the first esterification reaction tank was continuously taken out of the system and supplied to the second esterification reaction tank, and EG distilled from the first esterification reaction tank was supplied to the second esterification reaction tank in an amount of 8% by mass relative to the produced PET. Furthermore, an EG solution of magnesium acetate tetrahydrate containing 65 ppm of Mg atoms relative to the produced PET and an EG solution of TMPA (trimethyl phosphate) containing 40 ppm of P atoms relative to the produced PET were added, and the reaction was carried out at 260° C. with an average residence time of 1 hour under normal pressure. Next, the reaction product in the second esterification reaction tank was continuously taken out of the system and supplied to the third esterification reaction tank, and each of the 10% EG slurries was added using a high-pressure disperser (manufactured by Nippon Seiki Co., Ltd.) at 39 MPa (400 kg / cm 2) were dispersed 5 times under a pressure of 200°C and 0.2% by mass of porous colloidal silica with an average particle size of 0.9 μm and 0.4% by mass of synthetic calcium carbonate with an average particle size of 0.6 μm of ammonium salt of polyacrylic acid attached to 1% by mass relative to calcium carbonate, and reacted at 260°C at an average residence time of 0.5 hours under normal pressure. The esterification reaction product generated in the third esterification reaction tank was continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, filtered with a filter having sintered 95% stainless steel fibers with a cutting diameter of 20 μm, ultrafiltered and extruded into water, and cut into chips after cooling to obtain PET chips with a characteristic viscosity of 0.60 dl / g (hereinafter referred to as PET (I)). The lubricant content in the PET chip was 0.6% by mass.
[0264] (Preparation of polyethylene terephthalate particles (PET(II)))
[0265] On the other hand, in the production of the above-mentioned PET sheet, a PET sheet having an intrinsic viscosity of 0.62 dl / g and containing no particles of calcium carbonate, silicon dioxide, etc. (hereinafter referred to as PET (II)) was obtained.
[0266] (Manufacturing of Laminated Film X)
[0267] After drying, the PET sheets were melted at 285°C, melted at 290°C by a separate melt extruder, and subjected to two-stage filtration using a filter having 95% of sintered stainless steel fibers with a cut diameter of 15 μm and a filter having 95% of sintered stainless steel particles with a cut diameter of 15 μm, merged in a feed block, and laminated in such a manner that PET (I) became the anti-release side layer and PET (I) became the release side layer, extruded (cast) into a sheet at a speed of 45 m / min, and electrostatically bonded / cooled on a casting drum at 30°C by an electrostatic bonding method to obtain an unstretched polyethylene terephthalate sheet having an intrinsic viscosity of 0.59 dl / g. The layer ratio was adjusted to anti-release side layer / release side layer = 60% / 40% by calculation based on the discharge amount of each extruder. Next, the unstretched sheet was heated by an infrared heater and stretched 3.5 times in the longitudinal direction at a roll temperature of 80°C by using the speed difference between the rolls. Then, it was introduced into a tenter and stretched 4.2 times in the transverse direction at 140°C. Then, it was heat treated at 210°C in a heat setting zone. Then, it was relaxed 2.3% in the transverse direction at 170°C to obtain a biaxially stretched polyethylene terephthalate film X having a thickness of 31 μm. The Sa of the release side layer of the obtained film X was 23 nm, and the Sa of the anti-release side layer was 21 nm.
[0268] (Manufacturing of Laminated Film Y)
[0269] After drying, the PET sheets were melted at 285°C, melted at 290°C by a separate melt extruder, and subjected to two-stage filtration using a filter sintered with 95% of stainless steel fibers having a cut diameter of 15 μm and a filter sintered with 95% of stainless steel particles having a cut diameter of 15 μm, and then merged in a feed block, laminated in such a manner that PET (I) became the anti-release surface layer and PET (II) became the release surface layer, extruded (cast) into a sheet at a speed of 45 m / min, and electrostatically bonded / cooled on a casting drum at 30°C by an electrostatic bonding method to obtain an unstretched polyethylene terephthalate sheet having an intrinsic viscosity of 0.59 dl / g. The layer ratio was adjusted to anti-release surface layer / release surface layer = 60% / 40% by calculating the discharge amount of each extruder. Next, the unstretched sheet was heated with an infrared heater and stretched 3.5 times in the longitudinal direction at a roll temperature of 80°C by using the speed difference between the rolls. Then, it was introduced into a tenter and stretched 4.2 times in the transverse direction at 140°C. Then, it was heat treated at 210°C in a heat setting zone. Then, it was relaxed 2.3% in the transverse direction at 170°C to obtain a biaxially stretched polyethylene terephthalate film Y having a thickness of 31 μm. The Sa of the release side layer of the obtained film Y was 2 nm, and the Sa of the anti-release side layer was 26 nm.
[0270] (Production of Acrylic Polyol A)
[0271] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen blowing tube, 231 parts by mass of methyl methacrylate (MMA), 130 parts by mass of stearyl methacrylate (SMA), 100 parts by mass of hydroxyethyl methacrylate (HEMA), 33 parts by mass of methacrylic acid (MAA), and 1153 parts by mass of isopropyl alcohol (IPA) were added, and the temperature in the flask was raised to 80°C while stirring. The flask was stirred for 3 hours while maintaining the temperature at 80°C, and then 0.5 parts by mass of 2,2-azobis-2-methyl-N-2-hydroxyethylpropionamide was added to the flask. After nitrogen substitution was performed while the temperature in the flask was raised to 120°C, the mixture was stirred at 120°C for 2 hours.
[0272] Next, a 1.5 kPa decompression operation was performed at 120°C to remove unreacted raw materials and solvents to obtain an acrylic polyol. The flask was returned to atmospheric pressure and cooled to room temperature, and 1976 parts by mass of an IPA aqueous solution (water content 50% by mass) was added and mixed. Then, ammonia was added using a dropping funnel while stirring, and the acrylic polyol was neutralized until the pH of the solution was in the range of 5.5 to 7.5 to obtain an acrylic polyol A with a solid content concentration of 20% by mass. The Tg of acrylic polyol A is 88°C, the acid value is 87 mgKOH / g, and the hydroxyl value is 100 mgKOH / g.
[0273] (Manufacture of Oxazoline Crosslinking Agent B)
[0274] 460.6 parts of isopropanol were added to a flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube and a thermometer, and heated to 80°C while slowly circulating nitrogen. A monomer mixture consisting of 126 parts of methyl methacrylate, 210 parts of 2-isopropenyl-2-oxazoline and 84 parts of methoxypolyethylene glycol acrylate prepared in advance, and an initiator solution consisting of 21 parts of 2,2'-azobis(2-methylbutyronitrile) ("ABN-E" manufactured by Nippon Hydrazine Industry Co., Ltd.) and 189 parts of isopropanol were added dropwise from a dropping funnel for 2 hours and reacted, and the reaction was continued for 5 hours after the addition was completed. Nitrogen was continuously circulated during the reaction, and the temperature in the flask was maintained at 80±1°C. Then, the reaction solution was cooled to obtain a resin (B) having an oxazoline group with a solid content concentration of 25%. The amount of oxazoline groups in the obtained resin (B) having oxazoline groups was 4.3 mmol / g, and the number average molecular weight measured by GPC (gel permeation chromatography) was 20,000.
[0275] (Acrylic particles C-1)
[0276] Acrylic acid-based particle aqueous dispersion (manufactured by Nippon Shokubai Co., Ltd., trade name MX100W, average particle size 150 nm, solid content concentration 10% by mass)
[0277] (Acrylic particles C-2)
[0278] Acrylic acid-based particle aqueous dispersion (manufactured by Nippon Shokubai Co., Ltd., trade name MX300W, average particle size 450 nm, solid content concentration 10% by mass)
[0279] (Preparation of a slippery coating liquid)
[0280] An easy-lubricating coating liquid having the following composition was prepared.
[0281] (Easy-slip coating liquid)
[0282] Water 39.62 parts by mass
[0283] Isopropyl alcohol 35.00 parts by mass
[0284] Acrylic polyol resin A (solid content concentration 20% by mass) 16.57 parts by mass
[0285] Oxazoline crosslinking agent B (solid content concentration 25 mass%) 5.68 mass parts
[0286] Acrylic particles C-1 2.37 parts by mass
[0287] (Average particle size 150 nm, solid content 10% by mass)
[0288] Acrylic particles C-2 0.47 parts by mass
[0289] (Average particle size 450 nm, solid content concentration 10% by mass)
[0290] Surfactant D (silicone-based, solid content concentration 10% by mass) 0.30 parts by mass
[0291] (Release agent solution)
[0292] 100 parts by mass of a heat / UV curable silicone resin (LTC851 manufactured by Dow Corning Toray Co., Ltd.) and 2 parts by mass of a platinum catalyst (SRX212 manufactured by Dow Corning Toray Co., Ltd.) as a curing catalyst were diluted with a toluene / methyl ethyl ketone / heptane (=7:7:6) solution to prepare a release agent solution having a solid content of 2% by mass.
[0293] (Example 1)
[0294] (Manufacturing of Laminated Film Z)
[0295] As a film base polymer, PET resin pellets (PET (II)) having an intrinsic viscosity (solvent: phenol / tetrachloroethane = 60 / 40) of 0.62 dl / g and containing substantially no particles were dried at 135° C. for 6 hours under a reduced pressure of 133 Pa. Then, the pellets were supplied to an extruder, melt-extruded at about 280° C. into a sheet, and rapidly cooled and solidified on a rotating cooling metal roll whose surface temperature was maintained at 20° C. to obtain an unstretched PET sheet.
[0296] The unstretched PET sheet was heated to 100° C. using a heated roller group and an infrared heater, and then stretched 3.5 times in the longitudinal direction using a roller group having a peripheral speed difference to obtain a uniaxially stretched PET film.
[0297] Next, the easy-slip coating liquid was applied to one side of the PET film using a rod coater and dried at 80°C for 15 seconds. In addition, the coating amount after final stretching and drying was adjusted to 0.1 μm. Next, the film was stretched to 4.0 times in the width direction at 150°C using a tenter, heated at 230°C for 0.5 seconds while the length of the film in the width direction was fixed, and then relaxed at 230°C for 10 seconds at 3% in the width direction to obtain a polyester film Z with an easy-slip coating layer having a thickness of 31 μm. The Sa of the release side layer of the obtained film Z was 1 nm, and the Sa of the reverse release side layer was 6 nm.
[0298] (Formation of Release Coating Layer)
[0299] A release agent solution was applied to the surface of the polyester film with a slippery coating layer opposite to the surface on which the slippery coating layer was formed by a reverse gravure coater so that the thickness after drying would be 0.01 μm. The film was then dried with hot air at 120° C. for 30 seconds and immediately irradiated with ultraviolet light (300 mJ / cm 2 ), forming a release coating layer to obtain a release film.
[0300] (Formation of antistatic layer)
[0301] The antistatic layer-forming composition 1 described below was applied to the surface of the release film on which the slippery coating layer was formed by a reverse gravure coater in a manner to a thickness of 0.05 μm after drying, and then dried / cured with hot air at 140° C. for 30 seconds to obtain an antistatic release film. The structure in which the antistatic layer was formed on the reverse release layer via other layers was referred to as Structure 1.
[0302] (Antistatic layer forming composition 1)
[0303] Water 42.24 parts by mass
[0304] Isopropyl alcohol 42.24 parts by mass
[0305] Antistatic agent E-1 (polythiophene conductive polymer, solid content concentration 1.20 mass %)
[0306] 11.67 parts by mass
[0307] Thermosetting binder resin F-1
[0308] (Made by NIPPON CARBIDE INDUSTRIES CO., INC., melamine resin, full ether type, solid content concentration 70 mass %)
[0309] 0.80 parts by mass
[0310] Conductive additive G-1 (NMP) 3.00 parts by mass
[0311] Surfactant H-1 (manufactured by Nissin Chemical Industry Co., Ltd., Dynol 604, solid content concentration 100 mass %)
[0312] 0.06 parts by mass
[0313] After being wound as a release roll, the unwinding charge is low when it is unwound again for coating a ceramic sheet, and adhesion of environmental foreign matter can be suppressed, so that the yield of ceramic capacitors will not be reduced, and ceramic capacitors with good quality can be manufactured.
[0314] (Example 2)
[0315] An antistatic release film was obtained in the same manner as in Example 1 except that the thermosetting binder resin in the antistatic layer forming composition 1 used in Example 1 was changed to a thermosetting binder resin F-2 (manufactured by NIPPON CARBIDE INDUSTRIES CO., INC., melamine resin, iminomethylol type, solid content concentration 70% by mass) for using an antistatic layer forming composition 2.
[0316] (Example 3)
[0317] An antistatic release film was obtained in the same manner as in Example 1 except that the surfactant in the antistatic layer-forming composition 1 used in Example 1 was changed to H-2 (SURFYNOL SE-F manufactured by Nissin Chemical Industry Co., Ltd., solid content concentration 81 mass %).
[0318] (Example 4)
[0319] An antistatic release film was obtained in the same manner as in Example 1 except that the antistatic layer-forming composition 1 was changed to the antistatic layer-forming composition 4 described below.
[0320] (Antistatic layer forming composition 4)
[0321] Water 45.10 parts by mass
[0322] Isopropyl alcohol 45.10 parts by mass
[0323] Antistatic agent E-1 (polythiophene conductive polymer, solid content concentration 1.20 mass %)
[0324] 5.83 parts by mass
[0325] Thermosetting binder resin F-1
[0326] (Made by NIPPON CARBIDE INDUSTRIES CO., INC., melamine resin, full ether type, solid content concentration 70 mass %)
[0327] 0.90 parts by mass
[0328] Conductive additive G-1 (NMP) 3.00 parts by mass
[0329] Surfactant H-1 (manufactured by Nissin Chemical Industry Co., Ltd., Dynol 604, solid content concentration 100 mass %)
[0330] 0.06 parts by mass
[0331] (Example 5)
[0332] An antistatic release film was obtained in the same manner as in Example 1 except that the antistatic layer-forming composition 1 was changed to the antistatic layer-forming composition 5 described below.
[0333] (Antistatic layer forming composition 5)
[0334] Water 39.37 parts by mass
[0335] Isopropyl alcohol 39.37 parts by mass
[0336] Antistatic agent E-1 (polythiophene conductive polymer, solid content concentration 1.20 mass %)
[0337] 17.50 parts by mass
[0338] Thermosetting binder resin F-1
[0339] (Made by NIPPON CARBIDE INDUSTRIES CO., INC., melamine resin, full ether type, solid content concentration 70 mass %)
[0340] 0.70 parts by mass
[0341] Conductive additive G-1 (NMP) 3.00 parts by mass
[0342] Surfactant H-1 (manufactured by Nissin Chemical Industry Co., Ltd., Dynol 604, solid content concentration 100 mass %)
[0343] 0.06 parts by mass
[0344] (Example 6)
[0345] An antistatic release film was obtained in the same manner as in Example 1 except that the antistatic layer-forming composition 1 was changed to the antistatic layer-forming composition 5 described below.
[0346] (Antistatic layer forming composition 5)
[0347] Water 33.64 parts by mass
[0348] Isopropyl alcohol 33.64 parts by mass
[0349] Antistatic agent E-1 (polythiophene conductive polymer, solid content concentration 1.20 mass %)
[0350] 29.17 parts by mass
[0351] Thermosetting binder resin F-1
[0352] (Made by NIPPON CARBIDE INDUSTRIES CO., INC., melamine resin, full ether type, solid content concentration 70 mass %)
[0353] 0.50 parts by mass
[0354] Conductive additive G-1 (NMP) 3.00 parts by mass
[0355] Surfactant H-1 (manufactured by Nissin Chemical Industry Co., Ltd., Dynol 604, solid content concentration 100 mass %)
[0356] 0.06 parts by mass
[0357] (Example 7)
[0358] An antistatic release film was obtained in the same manner as in Example 1 except that the coating thickness was changed so that the thickness after drying would be 0.10 μm.
[0359] (Example 8)
[0360] An antistatic release film was obtained in the same manner as in Example 1 except that the coating thickness was changed so that the thickness after drying would be 0.15 μm.
[0361] (Example 9)
[0362] An antistatic release film was obtained in the same manner as in Example 1 except that the antistatic layer-forming composition 1 was changed to the antistatic layer-forming composition 7 described below.
[0363] (Antistatic layer forming composition 7)
[0364] Water 42.17 parts by mass
[0365] Isopropyl alcohol 42.17 parts by mass
[0366] Antistatic agent E-1 (polythiophene conductive polymer, solid content concentration 1.20 mass %)
[0367] 11.67 parts by mass
[0368] Thermosetting binder resin F-3
[0369] (Nisshinbo Chemical Inc., polycarbodiimide resin, solid content concentration 40% by mass)
[0370] 0.93 parts by mass
[0371] Conductive additive G-1 (NMP) 3.00 parts by mass
[0372] Surfactant H-1 (manufactured by Nissin Chemical Industry Co., Ltd., Dynol 604, solid content concentration 100 mass %)
[0373] 0.06 parts by mass
[0374] (Comparative Example 1)
[0375] An antistatic release film was obtained in the same manner as in Example 1 except that the antistatic layer-forming composition 1 was changed to the antistatic layer-forming composition 8 described below.
[0376] (Antistatic layer forming composition 8)
[0377] Water 19.30 parts by mass
[0378] Isopropyl alcohol 19.30 parts by mass
[0379] Antistatic agent E-1 (polythiophene conductive polymer, solid content concentration 1.20 mass %)
[0380] 58.33 parts by mass
[0381] Conductive additive G-1 (NMP) 3.00 parts by mass
[0382] Surfactant H-1 (manufactured by Nissin Chemical Industry Co., Ltd., Dynol 604, solid content concentration 100 mass %)
[0383] 0.06 parts by mass
[0384] (Comparative Example 2)
[0385] Except having changed the base material into X, it carried out similarly to Example 1, and obtained the antistatic release film.
[0386] (Comparative Example 3)
[0387] Except having changed the base material into Y, it carried out similarly to Example 1, and obtained the antistatic release film.
[0388] (Comparative Example 4)
[0389] An antistatic release film was obtained in the same manner as in Example 1 except that the substrate was changed to Y and the antistatic layer was not formed. The configuration in which the antistatic layer was not formed was referred to as Configuration 2.
[0390] (Comparative Example 5)
[0391] (Manufacture of polyester film)
[0392] As a film base polymer, PET resin pellets (PET (II)) having an intrinsic viscosity (solvent: phenol / tetrachloroethane = 60 / 40) of 0.62 dl / g and substantially free of particles were dried at 135° C. for 6 hours under a reduced pressure of 133 Pa. Then, they were supplied to an extruder, melt-extruded at about 280° C. into a sheet, and rapidly cooled and solidified on a rotating cooling metal roll whose surface temperature was maintained at 20° C. to obtain an unstretched PET sheet.
[0393] The unstretched PET sheet was heated to 100° C. using a heated roller group and an infrared heater, and then stretched 3.5 times in the longitudinal direction using a roller group having a peripheral speed difference to obtain a uniaxially stretched PET film.
[0394] Next, the easy-slip coating liquid was applied to one side of the PET film using a rod coater and dried at 80°C for 15 seconds. In addition, the coating amount after final stretching and drying was adjusted to 0.1 μm. Next, the film was stretched to 4.0 times in the width direction at 150°C using a tenter, heated at 230°C for 0.5 seconds while the length of the film in the width direction was fixed, and then relaxed at 230°C for 10 seconds at 3% in the width direction to obtain a polyester film Z with an easy-slip coating layer having a thickness of 31 μm. The Sa of the release side layer of the obtained film Z was 1 nm, and the Sa of the reverse release side layer was 6 nm.
[0395] (Formation of antistatic layer)
[0396] The antistatic layer-forming composition 1 described below was applied to the surface of the substrate Z not having the slippery coating layer (release layer) using a reverse gravure coater to a thickness of 0.05 μm after drying, and then dried / cured using hot air at 140° C. for 30 seconds to obtain an antistatic film.
[0397] (Formation of Release Coating Layer)
[0398] The surface of the antistatic film on which the antistatic layer was formed was coated with a release agent solution by a reverse gravure coater in such a manner that the thickness after drying was 0.01 μm, and then dried with hot air at 120° C. for 30 seconds, and then immediately irradiated with ultraviolet light (300 mJ / cm 2 ), a release coating layer is formed to obtain an antistatic release film. The structure in which an antistatic layer is provided on the release layer side of the substrate Z and a release layer is provided on the antistatic layer is referred to as Structure 3.
[0399] Table 1 shows the evaluation results of each example and comparative example.
[0400] [Table 1A]
[0401]
[0402] [Table 1B]
[0403]
[0404] Table 1 shows the mass ratio of the antistatic agent / thermosetting adhesive in the antistatic layer-forming composition, which is a mass ratio when the total solid content of the antistatic agent and the thermosetting adhesive is 100 mass %.
[0405] The embodiments and examples disclosed this time should be considered as illustrative in all aspects and not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments described above, and includes all modifications within the meaning and scope equivalent to the claims.
[0406] The object of the present invention is to provide a release film having an antistatic layer, wherein the antistatic layer has a highly smooth release surface and back surface, has good releasability, antistatic properties, slipperiness, and adhesion, has excellent antistatic properties and slipperiness even after long-term storage, and is difficult to fall off even when rubbed.
[0407] In Examples 1 to 9, the processed rolls are stored for a long time, and the unwinding charge is low when unwinding again, and environmental foreign matter is not easily attached, so good quality ceramic capacitors can be produced without reducing the yield of ceramic capacitors. In addition, since the antistatic layer is provided via the first functional layer, good powder shedding resistance and solvent resistance are obtained.
[0408] On the other hand, in Comparative Example 1, since the thermosetting binder resin specified in the present invention is not used, the adhesion to the substrate is poor, and even if an antistatic layer is provided across the first functional layer, the powder shedding and solvent resistance are also poor. In addition, if the unwinding charge after long-term storage is measured, there is a concern about the deterioration of the yield rate caused by the attachment of foreign matter. It is believed that this is due to poor adhesion, so the film roll repeatedly expands / contracts slightly during long-term storage, and the antistatic layer is cut off, thereby deteriorating the unwinding charge. Furthermore, it is believed that the antistatic layer affects the release layer, resulting in deterioration of the surface roughness and deterioration of the ceramic peeling evaluation.
[0409] In Comparative Examples 2 and 3, since the first functional layer is not interposed, the adhesion to the substrate is poor, and the powdering resistance and solvent resistance are poor. Therefore, if the unwinding charge measurement after long-term storage is performed, there is a concern that the yield rate will deteriorate due to the adhesion of foreign matter.
[0410] In Comparative Example 4, since no antistatic layer was provided, the unwinding charge after long-term storage became high, and there was a concern about deterioration in yield when manufacturing a thin ceramic green sheet.
[0411] In Comparative Example 5, since the antistatic agent was disposed between the substrate and the release layer, it is considered that the release layer was poorly cured and the peeling evaluation was poor.
[0412] Industrial Applicability
[0413] According to the present invention, a release film having a highly smooth release surface and back surface, having good releasability, antistatic property, slipperiness, adhesion, excellent antistatic property and slipperiness after long-term storage, and an antistatic layer that is not easy to fall off even when rubbed can be provided. In addition, by using the release film for manufacturing ceramic green sheets of the present invention, an extremely thin ceramic green sheet can be obtained, and a tiny ceramic capacitor can be efficiently manufactured.
Claims
1. A release film with an antistatic layer, comprising: a substrate, an antistatic layer provided on one surface of the substrate via a first functional layer, and a release layer provided on the other surface of the substrate, The antistatic layer is a layer formed of an antistatic layer-forming composition containing an antistatic agent and a thermosetting binder resin. The antistatic agent comprises a conductive polymer. The surface resistivity (logΩ / □) of the side provided with the antistatic layer is 3 or more and 10 or less.
2. The release film with an antistatic layer according to claim 1, wherein The substrate contains substantially no inorganic particles, The first functional layer is a slippery coating layer, The easy-slip coating layer comprises particles, The antistatic layer is disposed on one surface of the substrate via the easy-slip coating layer.
3. The release film with an antistatic layer according to claim 1, wherein The conductive polymer is a polythiophene conductive polymer.
4. The release film with an antistatic layer according to claim 1, wherein The thermosetting binder resin includes at least one selected from acrylamide resin, melamine resin, polycarbodiimide resin, and oxazoline resin.
5. The release film with an antistatic layer according to claim 1, wherein In the antistatic layer, when the total solid content of the antistatic agent and the thermosetting binder resin is set to 100 mass %, The content of the thermosetting binder resin is 40 mass % or more and 95 mass % or less.
6. The release film with an antistatic layer according to claim 1, wherein The surface roughness Sa of the surface of the antistatic layer on the opposite side to the substrate is 1 nm or more and 25 nm or less, and the maximum protrusion height P is 60 nm or more and 500 nm or less.
7. The release film with an antistatic layer according to claim 1, wherein The surface roughness Sa of the surface of the release layer on the opposite side to the substrate is 0.1 nm to 5 nm inclusive, and the maximum protrusion height P is 1 nm to 50 nm inclusive.
8. The release film with an antistatic layer according to claim 1, wherein The release film roll was stored at 40° C. and a humidity of 50% or less for 30 days and then unwound at a speed of 100 m / min. The charge amount was greater than −2 kV and less than +2 kV.
Citation Information
Patent Citations
Antistatic polyester film
JP1990073833A
antistatic polyester film
JP1995068388B2
Release film having antistatic function
JP2003251756A
Release film for ceramic green sheet manufacturing process
JP2012224011A
Mold release film
CN107249879A